2014
DOI: 10.3109/09537104.2014.934217
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of IL-12 and IL-23 in patients with primary immune thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is an acquired autoimmune disorder. Both impaired platelet production and T-cell-mediated effects play a role in ITP. A T-helper1 (Th1) polarization of the immune response and up-regulation of Th17 cells have been demonstrated in ITP patients. Interleukin (IL)-12 and IL-23 produced by antigen presenting cells are essential for inducing and sustaining Th1 and Th17 effector cells via different pathways. However, less is known with regard to the levels of expression and synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Interestingly, among the members of the IL‐12 family (which consists of IL‐12, IL‐23, IL‐27, and IL‐35), IL‐12 and IL‐23 are proinflammatory cytokines with important effects on Th1 and Th17 commitment, whereas IL‐27 and IL‐35 mainly exert immune regulatory functions 29 . Previous studies demonstrated that ITP patients had high levels of IL‐12 and IL‐23, whereas we here report lower serum IL‐27 and IL‐35 levels in newly diagnosed ITP patients, indicating that the imbalance of IL‐12 family member cytokines might be a cytokine profile signature in ITP patients 30 …”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Interestingly, among the members of the IL‐12 family (which consists of IL‐12, IL‐23, IL‐27, and IL‐35), IL‐12 and IL‐23 are proinflammatory cytokines with important effects on Th1 and Th17 commitment, whereas IL‐27 and IL‐35 mainly exert immune regulatory functions 29 . Previous studies demonstrated that ITP patients had high levels of IL‐12 and IL‐23, whereas we here report lower serum IL‐27 and IL‐35 levels in newly diagnosed ITP patients, indicating that the imbalance of IL‐12 family member cytokines might be a cytokine profile signature in ITP patients 30 …”
Section: Resultscontrasting
confidence: 67%
“…29 Previous studies demonstrated that ITP patients had high levels of IL-12 and IL-23, whereas we here report lower serum IL-27 and IL-35 levels in newly diagnosed ITP patients, indicating that the imbalance of IL-12 family member cytokines might be a cytokine profile signature in ITP patients. 30…”
Section: Cytokinesmentioning
confidence: 99%
“…Severe samples were also enriched for genes associated with an increased response to IL-12, a proinflammatory cytokine. JAK-STAT activation and subsequent IFN-γ generation, after IL-12 stimulation, have been previously reported in patients with immune thrombocytopenia ( 59 ).…”
Section: Resultsmentioning
confidence: 83%
“…Serum IL-37 levels and IL-18Rα + /CD4 + T-cell ratios are negatively correlated with PLT counts ( 102 ). IL-37 expression is significantly higher in patients with active ITP, and can regulate the expression of several cytokines to exert anti-inflammatory effects ( 103 ). In terms of the possible mechanisms involving IL-37 in the pathogenesis of ITP, it is speculated that IL-37 may promote Th2 cell function by influencing cytokine expression and inhibiting the immune response effects of Th1 and Th17, thereby alleviating the inflammatory responses.…”
Section: Il-37 and Aidsmentioning
confidence: 99%